DECRIMINALIZATION OF GAMBLING IN UKRAINE:: INTERNATIONAL EXPERIENCE - Grudzur, Oleg (2020)
The relevance of this article is due to the fact that the entertainment sphere is one of the most important components of filling the national and world sectors of the country’s economy. The purpose of the article is to carry out scientific research on the functioning and overall reform of the gambling business in Ukraine, to study foreign experience of developed countries of the world in this field. The leading research methods are general scientific and specific research methods, including methods of logic, analysis, comparison etc. The results of this study are to identify the socio-economic grounds for legalizing gambling business in Ukraine and to outline a national legal mechanism for improving activities in this field. The significance of the obtained results is reflected in the fact that this study may serve as a basis for outlining future changes to the current legislation of Ukraine on the gambling business functioning in Ukraine.